2017
DOI: 10.1167/iovs.16-20860
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Tilt, Crescent, Ovality, and Torsion in a Multi-Ethnic Cohort of Young Adults With and Without Myopia

Abstract: PurposeThe purpose of this article is to evaluate optic nerve head (ONH) characteristics in an ethnically diverse cohort of young U.S. adults.MethodsIn this study, 409 myopes and 206 nonmyopes (median age 22 years) completed measures including biometry and spectral domain optical coherence tomography from enface (ovality and torsion) and cross-sectional (tilt and crescent width) scans. Associated factors were evaluated using multivariable models.ResultsIn myopic versus nonmyopic right eyes, median tilt (6.0° v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…Tumors that only affect the ON are referred to as optic nerve gliomas (ONGs). In general, OPGs are uncommon and account for only about 1% of intracranial tumors [69]. However, they are the most common primary tumors of the optic nerve, comprising about 65% of all intrinsic ON tumors [70].…”
Section: Primary Tumors Of the Optic Nerve 41 Optic Pathway Glioma mentioning
confidence: 99%
See 2 more Smart Citations
“…Tumors that only affect the ON are referred to as optic nerve gliomas (ONGs). In general, OPGs are uncommon and account for only about 1% of intracranial tumors [69]. However, they are the most common primary tumors of the optic nerve, comprising about 65% of all intrinsic ON tumors [70].…”
Section: Primary Tumors Of the Optic Nerve 41 Optic Pathway Glioma mentioning
confidence: 99%
“…More than two-thirds of OPGs are detected in the first decade of life and up to 90% before the end of the second decade [69]. ONGs are most often benign and slowly growing.…”
Section: Primary Tumors Of the Optic Nerve 41 Optic Pathway Glioma mentioning
confidence: 99%
See 1 more Smart Citation
“…However, PPA -BM was associated with a longer axial length but not with glaucoma [2][3][4][5]. A previous study showed that optic nerve head (ONH) tilt was associated with PPA +BM and PPA -BM widths, which suggested that the microstructure of PPA might reflect the myopic remodeling of the ONH [6]. However, PPA's formation and significance are not fully understood.…”
Section: Introductionmentioning
confidence: 98%
“…However, PPA -BM was associated with a longer axial length but not with glaucoma [2][3][4][5]. A previous study showed that optic nerve head (ONH) tilt was associated with PPA +BM and PPA -BM widths, which suggested that the microstructure of PPA might reflect the myopic remodeling of the ONH [6]. However, PPA's formation and significance are not fully understood.…”
Section: Introductionmentioning
confidence: 98%